Secret level valuation method of BLP model based on some application properties - Chan DONG; Xiu-bin FAN; You-wen LI; Jian-rong WANG (Tongxin xuebao)
According to the access attribute properties between subjects and objects in the information system,a viable method of the BLP model secret level valuation was given,and two merging conditions were put forward.The mathematical model of subject-object secret level valuation under BLP model was established on the two merging conditions.When the condition solution was not the constant one,its expansion solution being not sure the global one was proved,but the approximate condition modification valuation solution could be obtained from it.Using the above results,one difficult problem from one national information system about the BLP model secret level valuation was solved.